Wearing the mask: The role of imposter phenomenon in EFL learning and its effect on learner emotions and engagement - Resnik, Pia; Dewaele, Jean-Marc; Botes, Elouise (Studies in Second Language Learning and Teaching, 2025)
The imposter phenomenon (IP), which is characterized by a sense of incompetence and self-perceived intellectual inferiority due to being unable to acknowledge one’s own achievements and abilities despite objective success, is widely recognized as a common experience with detrimental effects in academic settings. Yet, its role in the context of foreign language (FL) learning remains underexplored. This study investigates the role of the experience of IP among 397 tertiary-level FL learners of English, possible effects of demographic and language use variables, as well as the extent to which IP affects students’ foreign language enjoyment (FLE), their foreign language classroom anxiety (FLCA), and engagement with FL learning. Statistical analyses of data gathered with a web survey revealed that younger, female participants were more likely to experience IP, as were those who perceived their standing in the group of learners as below average. Additionally, latent modeling indicated that IP was linked to both FLCA and FLE, and it predicted the performance engagement of English as a foreign language (EFL) learners. Overall, this study provides evidence as to the presence of IP in EFL classrooms and makes a case for the variable to be included in further studies of the nomological network of individual difference variables.